Gas turbine theory - Cohen, Henry; Rogers, G. F. C.; Saravanamuttoo, H. I. H. (Harlow [England] : Longman, 1996)
This book is about: Shaft power cycles; Gas turbinr cycles for aircraft propulsion; Centrifugal compressors; Axial flow compressors; Combustion systems; Axial and radial flow turbines; Prediction of performance of simple gas turbines; and Prediction of performance-futher topics.
Keywords: Gas-turbines.; Gas-turbines.